Reflecting internalization and manifestation of Sundanese cultural values on leadership communication styles in the mining industry (an ethnographic study at PT Petrosea, Tbk.) - Fazarullah , Dwirizky; Heikal, Jerry (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This research explores the influence of Sundanese cultural values on leadership communication styles at PT Petrosea, a mining company in Indonesia. This qualitative research employs an ethnographic approach and involves three leaders at PT Petrosea who have a strong Sundanese cultural background. Data were collected through participant observation and in-depth interviews, and then analyzed qualitatively. The results show that Sundanese cultural values, such as